Odlat kött - Engström, Niklas; Gerner, Erik; Sander, Viktor (My University, 2009)
The production of cultivated meat likely has several benefits compared to conventional meat production, both environmental and ethical. There are, however, a number of problems that needs to be solved before cultivated meat can become marketable. One such aspect is to find a biodegradable scaffold for the cells to grow on in order to go beyond minced meat. The aim of this study is to examine whether it is possible to cultivate and differentiate muscle stem cells into fully developed muscle cells on starch microspheres. Furthermore, the effect of electrical pulses, with the purpose of enlarging the muscle cells, is examined. The cells are grown in regular cell cultivation dishes modified with electrodes of platinum connected to a pulse generator. The experimental results show that it is possible to cultivate and initiate differentiation of muscle stem cells into muscle cells on the starch microspheres. The effects of electric pulse stimulation could not be fully investigated, since the muscle stem cells in our experimental set-up did not completely differentiate into muscle cells.
Keywords: Cell- och molekylärbiologi; Industriell bioteknik; Cell and molecular biology; Industrial Biotechnology